ESTIMASI SUMBERDAYA BATUGAMPING DALAM KERANGKA SABUK FASIES KAJIAN DI DAERAH PAMUBULAN PROVINSI BANTEN - Nur Taufiqurrahman, Ahmad
Research on estimation of limestone resources is heavily concentrated on geostatistical analysis. The entire limestone body is estimated using a certain estimation method and it is expected that grade prediction can be carried out well. However, the limestone body is not a homogeneous edifice, there are variations both vertically and horizontally. The various depositional conditions are reflected in the different facies and facies belts. This study attempts to previously separate the limestone body as a whole into facies belts, after which estimation is carried out using the geostatistical method. An investigation was conducted in the northern Pamubulan area, Banten Province. Research location has an area of about 93 hectares. All 67 surface geological observation locations were successfully collected. There are 15 drilling points carried out in search of limestone potential. Drilling depths range between 75 and 150 meters. Total rock intercepts reach 1,697.5 meters. Detailed core descriptions were carried out on all samples of core rock that were excavated. Overall, 538 rock samples were sent to the laboratory for XRF testing. The oxides examined were CaO, MgO, SiO2, Fe2O3, and Al2O3. This study only estimates the grade of CaO and MgO. This is considered sufficient to identify the suitability of limestone demanded by the cement industry. Carbonate rocks in the study area can be divided into six facies and 31 subfacies. The boundstone facies is interpreted as sediments from the reef environment. Grainstone and packstone facies are generally found in the environment around the reef, such as carbonate sand shoal. Mudstone and wackestone facies tend to be on interior platforms. The carbonate breccia facies is interpreted as a slope and or toe of slope deposit. Geological modeling was initially carried out by creating an interior platform facies belt body as a simplification of the restricted and normal marine platform interior. The platform margin is a combination of the reef margin facies belt and sand shoals. The last is the platform slope, a fusion of the slope facies belt and the toe of slope. Domaining is based on these three facies belts. 12 limestone models have been identified. Ten of them are platform margin facies belts separated by position and changes in geochemical properties. One facies belt was a wide interior platform that serves as the background of all study areas and covers almost all of the existing facies belts. This facies belt is found in the southwest and thickens to the southeast. The last is the platform slope facies belt which is located in the northeast of the study area. Platform margin deposits are divided into two distinct geochemical properties. One has high CaO content with low MgO and low Al2O3, but the other has low CaO with high MgO. Interior platform deposits mostly have high levels of CaO, low MgO, and increased Al2O3. Interestingly, there is an interior platform deposit that has increased SiO2. The slope/toe of slope deposits are little known but have diverse geochemical constituents, especially CaO and MgO. Existing CaO and MgO grades will be constrained by each domain of the facies belt, so the estimation will only calculate those within each domain. This constraining succeeded in separating the bimodal grade data into unimodal, a chemical grade that is more suitable to be processed in a later estimation stage. The inverse distance weighting method is used in the estimation process. 220 million tons of limestone resources are estimated to be suitable for cement production. Only CaO levels of more than 40% and MgO of less than 5% are included in the estimation.